THE ROLE OF EXTENSION IN CHANGING THE DAIRY INDUSTRY IN PAKISTAN: A REVIEW - S. Ahmad; G. Hinch; J. Prior; P. Thomas; D. Burrell (Journal of Animal and Plant Sciences, 2012)
Pakistan is primarily an agricultural based country, and livestock plays a pivotal role in its economy by providing essential items of the human diet in the form of milk, meat and eggs. The population of the country is nearly180 million, and 36 million in the rural areas depend directly on the livestock and dairy sectors. Pakistan has recently been ranked as the world’s third largest milk producer, with the recent growth in per capita milk production being driven by an increase in the number of dairy animals rather than by milk yield improvement. The current growth in population and increasing demand for food has created the need to produce more milk. Pakistani dairy farmers need to be aware of the key drivers of future change so that they can plan for increasing demand. This review is focused on the key factors influencing the change in the dairy industry and the role of extension in the change process. The important factors influencing the dairy sector from extension professionals point of view is capacity development through participatory principles. From dairy farmers’ perspectives, shift from traditional practices towards improved sustainability and food security. Government and NGOs need to invest in the sector and avoid duplication and infiltration of dairy programs across the country. The potential for further utilization of new technologies for farmers with the assistance of dairy extension services is highlighted.
Keywords: Dairy; extension methods; drivers of change; milk production; Pakistan; development